Quality of work life through sustainability options (Research, Society and Development, 2020)
When talking about Corporate Social Responsibility (CSR) it is necessary to analyze about QVT, since social welfare is also linked to the well-being of employees. The QVT associated with sustainability presents most of its studies in the area of engineering. The theme is still gaining ground in the publications of Administration and Social Sciences, which represents a gap to be explored by new researches. Given this scenario, this research contributes to improving the health of workers and their productivity, contributing to a better understanding of the relationship between company, employee and sustainable practice. The approach chosen was that of a qualitative method. The data collection instrument consisted of a script containing open guiding questions, based on the perspective of Walton and the social dimension of the Ethos Indicators for sustainable and responsible businesses. The research findings revealed that the company surveyed, even though it did not have a formal QLT program, offers a good quality of life outside of work to its employees and that although the company does not formally express practices regarding sustainability, the company's actions go to meeting of what is advocated in socio-environmental sustainability.